Biomarkers of folate and vitamin B12, alcohol intake and breast cancer risk: report from the EPIC cohort - Matejcic, M; Ricci, C; Perrier, F; Huybrechts, I; Buckland, G; Amiano, P; Zeleniuch-Jacquotte, A; Gylling, B; Sieri, S; Key, T; van Gils, C; Peeters, P; et al. (Wiley, 2017)
Background. B vitamin status and their interaction with alcohol were suggested to play a role in breast carcinogenesis; however, results from epidemiological studies have been inconsistent. We investigated the association between biomarkers of folate and vitamin B12 and the risk of breast cancer (BC) in a nested case-control study within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Methods. Microbiological assays were used to determine plasma concentrations of folate and vitamin B12 in 2,491 BC cases individually matched to 2,521 controls among women participants to the EPIC study who provided baseline blood samples. Multivariable conditional logistic regression models were used to estimate odds ratios by quartiles of plasma B vitamins. Subgroup analyses by menopausal status, hormone receptor status of breast tumors (ER, PR, and HER2), levels of alcohol intake, and MTHFR polymorphisms (677C>T and 1298A>C) were also performed. Results. Plasma concentrations of folate and vitamin B12 were not significantly associated with the overall risk of BC. No significant association emerged by hormone receptor status. A borderline positive association was observed between plasma concentrations of vitamin B12 and BC risk in women consuming above the median level of alcohol (ORQ4-Q1 = 1.30; 95% CI 1.03-1.64; Ptrend = 0.051). Plasma concentrations of vitamin B12 were also marginally associated with BC risk in women with plasma folate levels below the median value (ORQ4-Q1 = 1.26; 95% CI 1.00–1.60; Ptrend = 0.014). However, no significant heterogeneity between subgroups of alcohol intake (Pheterogeneity = 0.14) and plasma folate (Pheterogeneity = 0.059) was found. The association between MTHFR polymorphisms and BC risk in a subsample of this study population was not statistically significant. Conclusions. The present study raises the possibility for a role of vitamin B12 in the etiology of BC, and provides support for potential interactions between nutrients involved in one-carbon metabolism.